Analysis Of Archival Sources On The History Of The Establishment Of A Museum In Shakhrisabz (The Journal of Interdisciplinary Human Studies, 2026)
This article is devoted to the history of the formation of the museum and museum-reserve operating on the basis of a concept specializing in the history of Uz- bekistan in the 2,700-year-old city of Shahrisabz, which is included in the UNESCO World Heritage List. The chronological scope of this study covers the period from the beginning of the XX century to the beginning of the XXI century. Archival materials related to the political, cultural, and scientific processes of both Soviet Uzbekistan and independent Uzbekistan serve as the primary basis for revealing the historical process- es of the institution’s formation. The main objective of this study is to introduce to the wider public archival doc- uments concerning the initiatives undertaken after the Second World War to establish new museums in Uzbekistan, documents demonstrating that these initiatives were sub- ordinated to ideological objectives, and sources concerning the individuals who par- ticipated in this process. At the same time, the article highlights scholarly research on the museum’s activities and the contributions of individuals involved in its development during the period of Uzbekistan’s independence. The study employs a comparative analysis of archival materials, newspapers and journals, expedition reports, and the results of various scholarly studies to examine the nature of historical processes and the factors influencing their development. It analyzes newly identified sources concerning the efforts to establish a museum in Shahrisabz between 1946 and 1970, as well as the stages of the museum’s development and infor- mation about its founders during the period from 1996 to 2025.
Keywords: Shahrisabz Museum; Cultural and Educational Committee; agitation; “Hudjum” Factory; Uzkomstaris. 500 www.mijournals.com E-ISSN 3069-8375 Vol. 2; (Issue 9/2026)